A qualitative study of the psychological processes in patients with post-herpetic neuralgia - Wu Jun; Yang Zhi-Lan (Sciendo, 2021)
To understand the psychological process of patients with post-herpetic neuralgia (PHN) and provide references for the psychological management of PHN.